Malaysia : Financial Sector Stability Assessment. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This assessment is a review of the financial environment of Malaysia. Like many other Asian countries, Malaysia experienced financial distress in the late 1990s, but the country's policy reforms have moved it to a successful economy. A ten-year financial plan (2001-10) by Bank Negara Malaysia restructured the financial sector. Banks were well capitalized, household debts were strengthened, and securities and insurances were developed. Malaysia thus became the global center for Islamic finance. The authorities look on to a developed Malaysia by 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet